Mendeteksi Potensi Sumber Daya Air Sebagai Pembangkit Listrik Tenaga Air Melalui Pembelajaran Project Penguatan Profil Pelajar Pancasila - Umam, Muhamad Safiul (Universitas Pendidikan Ganesha, 2024)
Water resources are potential that can be developed as energy to drive turbines in hydroelectric power plants. The fact is that Sinaka Village is experiencing an electricity crisis, only 28.57% of the village area has electricity. Detecting the potential of water resources can be done through project-based learning to strengthen the profile of Pancasila students. This research aims to: (1) analyze the methods used in calculating water resource potential; (2) classifying the potential for generated power as a hydropower energy source and (3) analyzing the socio-economic impacts that can be obtained by society. There are six classifications of hydropower, namely pico hydro, micro hydro, mini hydro, small hydro, medium hydro, large hydro. The research method is a field survey using observation, mapping, measurement, interviews, documentation studies and literacy studies. Water discharge is analyzed using the formula Q = V/t, while water resources are analyzed using the formula P = 9.8 x Q x Heff (W). The floating method was used to calculate the average speed of water flow (0.2 m/s), then the water bit was analyzed to obtain a generated power of 1,155,127.5 Watts which is included in the small-hydro hydropower classification. The social economic potential that can be obtained is: (1) affordable monthly fees; (2) absorb local workers; (3) the realization of energy independence and (4) the realization of water resources conservation areas.